Listening Comprehension by using Video in Online Class through WhatsApp - Lusi Marleni; Nurhidayah Sari; Vitri Angraini Hardi (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to determine whether there is an effect of using video as media on the students’ listening comprehension in an online class in the academic year 2020/2021. This research is pre-experimental. It involved 24 students in class. The class was taught by using video as media as the treatment in the class. The data were analyzed quantitatively by using the T-test formula. The result shows that the students listening comprehension in the post-test are higher than pre-test. The data analysis can be seen in many students who get a good score in the class by using video. It can be concluded that video in teaching listening comprehension in an online class is an influential media. As aresult, ????????????????????????is 7,03 and ????????????????????????is 1,68. In this case, the average score is 72. The use of video for listening comprehension is one of the alternative media in online class.